The unique family law in the state of Israel - Kohen, Yitsḥaḳ (Touro University Press, 2021)
Issues Subject to Modification in Family Law -- The Right of a Minor to Independent Status -- Extramarital Relationships and the Theoretical Rationales for the Joint Property Rules -- Property Sharing Arrangements in Israeli Family Law -- Recognition of Foreign Civil Marriages -- The Development of the Issue of Same-Sex Couples -- The Issue of Document Disclosure in General Court and in Family Court,